Situações fotográficas: a imersão do corpo no espaço como forma - Oliveira, Francisco Diêgo Vieira de (2019)
Situações fotográficas is a project that seeks to investigate the immersion of the body as sculpture in everyday spaces, providing performative situations focused on photography. It arises from the interest in approaching the exhibition space of galleries, sually predestined to be of the viewer, as a possible way of becoming / being art, and the spectator as participant, besides approaching the photography in the enlarged field before the image freeze, bringing as theoretical reference the writings of Stéphane Huchet. The research uses the A/r/tography approach, from the thought of Dias and Irwin, and is presented in a catalog-book format, bringing a brief survey of contemporary artists, and even young people on the art circuit, who work with expanded photography and performances focused on video and photography. For the accomplishment of the practical part, Instagram and the hashtag #SituaçõesFotográficas were used as a means of interaction between artist and spectator-participant, for the collection of images realized by the users of the platform as project experiment. As an artistic reference we bring the French Marcel Duchamp together with the Brazilians Rosangela Rennó, Cildo Meireles, Regina Silveira, among others who also discuss in their works questions related to the space of the work and the space of the spectator, which Aumont presents us as plastic space and exhibition space.